A PENANAMAN NILAI MORAL ISLAM KYAI DAN SANTRI DALAM TINJAUAN PSIKOLOGI ISLAM: PENANAMAN NILAI MORAL ISLAM KYAI DAN SANTRI - mahmud fauzi, mahmud (Asosiasi Psikologi Islam (API) Himpsi, 2020)
Kyai and santri are one of the subjects of Islamic education in pesantren, the main object of the pesantren is to instill ahklaqul karimah according to the Qur'an, Hadith, ijma' and qiyas Ulama'. This study aims to see the suitability between the practice of Islamic education and concept of Islamic psychology in teaching Islamic morals to students. This research method is a phenomenological study and data collection using in-depth interviews and analyzed with Islamic Psychology review. The results of this study indicate that the application of teaching Islamic moral to students by kyai and ustadz / ustadzah with Islamic psychological theory or An nafs in according with the basic quran and hadith is close to conformity. The things are found, namely: 1. the activity of reciting classical books such as ahklaq, tasawuf and tafsir and hadith. 2. The attitudes and actions of the ustadz / ustadzah dominan in punishment are feared to affect the physical and mental development of the students in the future. 3. The attitude of Tabayyun, khusnudhan and patience ustadz / ustadzah in cariying students/santri. 4. Ustadz / ustadzah must have a role model from Rosulullah Saw. Keywords : Islamic Moral, An Nafs, Islamic Boarding School